2019
DOI: 10.3171/2018.6.jns181045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of balloon guide catheter utilization on contact aspiration thrombectomy

Abstract: OBJECTIVEThe role of the balloon guide catheter (BGC) has not been evaluated in contact aspiration thrombectomy (CAT) for acute stroke. Here, the authors aimed to test whether the BGC was associated with recanalization success and good functional outcome in CAT.METHODSAll patients who had undergone CAT as the first-line treatment for anterior circulation intracranial large vessel occlusion were retrospectively identified from prospectively maintained registries for six stroke centers. The patients were dichoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 22 publications
3
46
0
1
Order By: Relevance
“…Finally, the role of BGC use was confirmed as the only independent predictor of FPR in these frontline CAT data. As mentioned earlier, this result concurred with previous studies that used frontline SRT 14 26–29. A recent meta-analysis focusing on the impact of BGC on outcomes showed that BGC use during EVT was associated with superior clinical (higher mRS 0–2) and angiographic outcomes (higher FPR, TICI 2b/3, lower number of passes, mortality, and shorter procedure time) 33.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, the role of BGC use was confirmed as the only independent predictor of FPR in these frontline CAT data. As mentioned earlier, this result concurred with previous studies that used frontline SRT 14 26–29. A recent meta-analysis focusing on the impact of BGC on outcomes showed that BGC use during EVT was associated with superior clinical (higher mRS 0–2) and angiographic outcomes (higher FPR, TICI 2b/3, lower number of passes, mortality, and shorter procedure time) 33.…”
Section: Discussionsupporting
confidence: 88%
“…Considering that the key elements of CAT are ‘clot contact’ and ‘aspiration force’, a larger luminal diameter can theoretically increase the contact area and generate a more intense aspiration force,25 which may result in a higher incidence of FPR in the COMPASS trial 14. Additionally, BGC use was consistently associated with FPR in previous frontline SRT studies and in the present study 14 26–29…”
Section: Discussionmentioning
confidence: 54%
“…A recent analysis compared data of the BGC and the CGC groups in frontline CAT cases using a Korean multi-center registry 25) . In the study, a total of 429 patients were enrolled, with the BGC used in 45.2% of patients.…”
Section: Balloon Guide Catheter In Catmentioning
confidence: 99%
“…Recently, stent retrievermediated mechanical thrombectomy (SR-MT) is considered the standard-of-care for selected patients with acute LVO in the anterior circulation due to positive results of recent five randomized clinical trials (RCT) 2,4,16,22,52) . A Direct Aspiration J Korean Neurosurg Soc 63 (1) : [14][15][16][17][18][19][20][21][22][23][24][25] First Pass Technique (ADAPT) or contact aspiration thrombectomy (CAT) using large bore catheters is also employed as another frontline treatment for LVO 12,24,32) . During the evolution of thrombectomy strategies, the versatile uses of 8 F or 9 F balloon guide catheters (BGC) in different clinical setups have been recognized as BGCs can be paired with a single clot retriever system 23,48) or combined with other adjunctive thrombectomy procedures 15,37,39) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation